Heart rate variability as an alternative indicator for identifying cardiac iron status in non-transfusion dependent thalassemia patients - Karn Wijarnpreecha (2018)
© 2015 Wijarnpreecha et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. Background: Iron-overload cardiomyopathy is a major cause of death in thalassemia patients due to the lack of an early detection strategy. Although cardiac magnetic resonance (CMR) T2∗ is used for early detection of cardiac iron accumulation, its availability is limited. Heart rate variability (HRV) has been used to evaluate cardiac autonomic function and found to be depressed in thalassemia. However, its direct correlation with cardiac iron accumulation has never been investigated. We investigated whether HRV can be used as an alternative indicator for early identification of cardiac iron deposition in thalassemia patients. Methods: Ninety-nine non-transfusion dependent thalassemia patients (23.00 (17.00, 32.75) years, 35 male) were enrolled. The correlation between HRV recorded using 24-hour Holter monitoring and non-transferrin bound iron (NTBI), hemoglobin (Hb), serum ferritin, LV ejection fraction (LVEF), and CMR-T2∗ were determined. Results: The median NTBI value was 3.15 (1.11, 6.59) μM. Both time and frequency domains of HRV showed a significant correlation with the NTBI level, supporting HRV as a marker of iron overload. Moreover, the LF/HF ratio showed a significant correlation with CMR-T2∗ with the receiver operating characteristic (ROC) curve of 0.684±0.063, suggesting that it could represent the cardiac iron deposit in thalassemia patients. HRV was also significantly correlated with serum ferritin and Hb. Conclusions: This novel finding regarding the correlation between HRV and CMR-T2∗ indicates that HRV could be a potential marker in identifying early cardiac iron deposition prior to the development of LV dysfunction, and may be used as an alternative to CMR-T2∗ for screening cardiac iron status in thalassemia patients.